On the association between modes of mental representation and mathematics experience in pre-service education students. - Gurney, Penelope J. (University of Ottawa (Canada), 1992)
The purpose of this study is to examine one aspect of the cognitive development of pre-service education students; i.e. the ability to utilize different modes of mental representation. This study attempts to provide a basis for understanding the relationship between the degree of experience in mathematics and the ability to utilize different modes of mental representation. The selected instrumentation illustrates different aspects of mental representation. The "Modes of Thought Questionnaire" (MOTQ) of Aylwin (1985) is allied to thinking itself, the "Knowledge Accessing Modes Inventory" (KAMI) of Rancourt (1989) is allied to knowledge accessing, and the Diehl and England (1958) version of the "Griffitts Test of Mental Imaging" is allied to mental imaging. In the MOTQ, associations were found between the level of experience in mathematics and both the ability to utilize each mode of mental representation and the overall use of the preferred modes. Specifically, a lack of experience in mathematics appears to be related to an ability to utilize correctly all three modes of mental representation when directed to do so. A lack of mathematics experience also appears to be related to a lower utilization of the verbal mode of mental representation, and a higher use of the visual mode, than expected. In the KAMI test, likewise, an association was found between levels of experience in mathematics and the dominant mode of knowledge accessing. A significantly higher percentage of subjects with no experience in mathematics have the noetic mode as dominant mode, whereas a significantly higher percentage of subjects with a high level of experience in mathematics have the rational mode as dominant mode. In the Griffitts test, however, no association was found between the level of experience in mathematics and the use of the three modes of mental imaging. This study has implications both for future research and for education. First, it gives a clear indication that differences do exist between the mental representation modes preferred by individuals with no mathematics experience as compared to those who have even a small level of experience in mathematics. Second, it provides implications regarding teacher education in Ontario, which arise from these differences in the utilization of all of the modes of mental representation and knowledge acquisition.
Keywords: Education, Educational Psychology.